FENOMENA PELANGGARAN KODE ETIK JURNALISTIK PASAL 12 TAHUN 2008 DI MEDIA ONLINE MANADO POST - Tatipang, Raynal A. (ACTA DIURNA KOMUNIKASI, 2013)
What is the ethic codes of journalistic, is not understand fully by the young journalists. They lack of understanding on plagiarism in particular. There are two cases remarkable to note for young journalists. Firstly, on the function of the ethic codes for journalists, and secondly, on the affectivity of carrying out the ethic code for journalists. Therefore, the young journalists has to learn and practices the ethic codes.